Kecenderungan dehidrasi pada remaja obesitas - Fitranti, Deny Yudi; Dieny, Fillah Fithra; Panunggal, Binar; Sukmasari, Vintantiana; Nugrahani, Gardinia (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2018)
Background : The content of water in fat cells in obese people is lower than muscle cells so that obese people are more easily dehydrated.Objective : The purpose of this study is to determine the risk factors of dehydration in adolescents.Methods : This study was a cross sectional study which began with screening of 168 students at SMA N 1 and 2 Semarang and found 63 students fulfilled the inclusion criteria. Subjects were selected by consecutive sampling. The dependent variable of this study is hydration status measured by the urine spesific gravity method. The independent variables consisted of obesity status that determined by the BMI/Age Z-score value, fluid intake was assessed using Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), physical activity was assessed using physical activity questionnaire, whereas knowledge regarding fluid was assessed by questionnaire. Data were analyzed using Chi Square test.Results ; There were 52,4% (n=33) subjects who were obese and only 9,5% (n=6) subjects were well-hydrated. The incidence of dehydration in obese adolescents (63,6%) was higher than non obese adolescents (36,7%). Obese subjects was 1.73 times more dehydrated than non obese subjects. Subject with deficiency of fluid intake was 1,85 times more dehydrated than subject with adequate fluid intake. Knowledge regarding fluid and physical activity was not a risk factor for dehydration in adolescents.Conclusion :Obesity and inadequate fluid intake ia risk factor for dehydration in adolescents